Knowledge, attitude and preventative practice of tuberculosis in rural communities of Dikgale, Mamabolo and Mothiba health and demographic surveillance system in Limpopo province, South Africa - Ngwanamohuba Mologadi Seloma; Marema Ephraim Makgatho; Eric Maimela (BMC, 2023)
Abstract Background Tuberculosis continues to be a serious public health issue. To reduce the transmission of the disease, it is imperative to address the major obstacle of inadequate understanding regarding the causes, risk factors, treatments, and prevention of pulmonary TB. The study assessed knowledge, attitude, and preventative practices of tuberculosis among community members in Dikgale, Mamabolo and Mothiba (DIMAMO) Health Demographic Surveillance system, Limpopo Province South Africa. Methods A cross-sectional clinic-based survey involving 360 participants was conducted at clinics at Dikgale, Mamabolo and Mothiba (DIMAMO) Health and Demographic Surveillance System. A standardised questionnaire on socio-demographic, knowledge, attitude and preventative practices towards tuberculosis based on (WHO) KAP-TB template guidelines was used to collect data. Descriptive statistics on Statistical Package for Social Sciences (SPSS) version 27.0 was used to analyse data. Results The results of the cross-sectional survey on KAP-TB illustrated that the participants have good knowledge, attitude, and perception of TB. Majority of the participants (n = 270, 75%) had good general knowledge, while (n = 90, 25%) had poor knowledge about TB. However, the study reports (n = 57, 15.6%) having knowledge of causative agents of TB. Participants showed a favourable attitude toward people who are infected with TB. 87% showed a favourable attitude while only 12.46% showed an unfavourable attitude towards TB. Participants showed a good practice of (71.7%) while (28.3%) of participants had poor practice towards TB. Conclusion Health education interventions programme on TB needs to be intensified among the community members to improve TB awareness and reduce transmission. Focused educational interventions on TB aetiology and mode of transmission are required to increase TB preventative practices and improve health-seeking behaviour among community members.